Mathematical modelling of thermal and flow processes in vertical ground heat exchangers - Pater Sebastian; Ciesielczyk Włodzimierz (Chemical and Process Engineering)
The main task of mathematical modelling of thermal and flow processes in vertical ground heat exchanger (BHE-Borehole Heat Exchanger) is to determine the unit of borehole depth heat flux obtainable or transferred during the operation of the installation. This assignment is indirectly associated with finding the circulating fluid temperature flowing out from the U-tube at a given inlet temperature of fluid in respect to other operational parameters of the installation.